2013
DOI: 10.1179/1743280412y.0000000010
|View full text |Cite
|
Sign up to set email alerts
|

Review of Bi2O3 based glasses for electronics and related applications

Abstract: The present work critically reviews the scientific and patent literature on low melting bismuth based oxide glass frits in materials for electronics, sensors and related applications such as sealing glasses, solar cells, architectural and automotive glass, the main motivation being to replace lead based materials by environmentally more benign ones. Due to similar glass forming properties of Bi and Pb, Bi based glasses are the closest 'drop-in' alternative for lead bearing formulations, and are therefore actua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(85 citation statements)
references
References 403 publications
0
85
0
Order By: Relevance
“…This value for the CN is reasonably near the value found in the EXAFS data fit (~2.0 ± 0.7) Å and can be easily interpreted from a geometrical point of view. Indeed, among the various coordination polyhedra found around Bi in oxides, a structure consisting of a trigonal O pyramid with the electron lone pair positioned opposite to the oxygen atoms plane was reported [33]. It is therefore reasonable to infer that Bi in the glassy matrix has 3-coordinated sites with a 3+ valence state.…”
Section: Resultsmentioning
confidence: 97%
“…This value for the CN is reasonably near the value found in the EXAFS data fit (~2.0 ± 0.7) Å and can be easily interpreted from a geometrical point of view. Indeed, among the various coordination polyhedra found around Bi in oxides, a structure consisting of a trigonal O pyramid with the electron lone pair positioned opposite to the oxygen atoms plane was reported [33]. It is therefore reasonable to infer that Bi in the glassy matrix has 3-coordinated sites with a 3+ valence state.…”
Section: Resultsmentioning
confidence: 97%
“…Nowadays, it has been well recognized that Bi2O3 oxide is one of the important constituents for the design and control of optical, electrical, and thermal properties of oxide glasses, and numerous studies on Bi2O3-based glasses have been studied so far (Dumbaugh, 1985;Maeder 2013). The most attractive features of Bi2O3 oxide are a large electronic polarizability and a weak single bond strength of Bi-O bonds (Dimitrov and Komatsu, 1999Komatsu et al, 2010).…”
Section: Frontiers Of Laser Pattering Of Crystals In Bi 2 O 3 -Based mentioning
confidence: 98%
“…In this paper, we demonstrated that Bi2ZnB2O7 crystal lines with a high orientation were patterned in Bi2O3-ZnO-B2O3 glasses by laser irradiations for the first time. Glasses based on the Bi2O3-ZnO-B2O3 system have also received much attention as new low-melting and shielding glasses (Maeder, 2013), and from this point of view, the understanding of the crystallization behaviors of Bi2O3-ZnO-B2O3 glasses is extremely important. The laser patterning of functional crystals in Bi2O3-based glasses has a great potential in application of nonlinear optical integrated devices (Liu et al, 2015) and is at the frontiers of glass science and technology in Bi2O3-based glasses.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, works related to bismuth oxide (Bi 2 O 3 ) have doubled in the last decade, thus reflecting the scientific, technological, and industrial importance of this compound. Its peculiar properties, including a large energy gap, a high refractive index and dielectric permittivity, and good photoconductivity [1][2][3][4][5][6], have made Bi 2 O 3 suitable for a large range of applications, such as optical coatings, photovoltaic cells, microwave integrated circuits, fuel cells, oxygen sensors, oxygen pumps, and catalytic activity [3,[7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%